Liquid compression molding or encapsulant compositions

The thermosetting resin composition, featuring a clathrate with a tetrakisphenol compound and imidazole, enhances warpage resistance and viscosity stability in LCM encapsulation agents, addressing key challenges in semiconductor packaging.

JP2025060995APending Publication Date: 2025-04-10HENKEL KGAA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2025000096
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2018-08-17
Filing Date
2025-01-06
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

Existing liquid compression molding (LCM) encapsulation agents face challenges with warpage resistance and viscosity stability, particularly in semiconductor packaging, where warping issues lead to defective packages and viscosity instability complicates manufacturing.

Method used

A thermosetting resin composition is developed, comprising a thermosetting resin matrix, a filler, and a curing component that includes a clathrate with a tetrakisphenol compound and a nitrogen-containing curing agent like imidazole. This composition exhibits improved viscosity stability and reduced warping, with specific properties such as low storage modulus, low coefficient of thermal expansion, and a glass transition temperature above 135°C.

Benefits of technology

The composition achieves significant improvements in warpage resistance, with a warp of less than 3 cm after curing, and maintains viscosity stability with a change of less than 30% over 24 hours at room temperature, addressing critical challenges in semiconductor packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025060995000036
    Figure 2025060995000036
  • Figure 2025060995000001
    Figure 2025060995000001
  • Figure 2025060995000002
    Figure 2025060995000002
Patent Text Reader

Abstract

To provide thermosetting resin compositions useful for liquid compression molding encapsulation of a reconfigured wafer.SOLUTION: A thermosetting resin composition comprises a thermosetting resin matrix, a silica filler, and a cure component comprising the combination of a clathrate comprising the combination of a tetrakis phenol compound(s) and a nitrogen-containing curing agent. The encapsulated molded wafer offers improved resistance to warpage, compared to reconfigured wafers encapsulated with known encapsulation materials.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] A thermosetting resin composition useful for liquid compression molding ("LCM") or encapsulation applications is provided that provides improved warpage resistance compared to LCM or encapsulation with known materials. [Background technology]

[0002] (Brief Description of Related Art) As semiconductor packaging evolves, the requirements for encapsulation materials are changing. To protect electronic components such as semiconductor devices, traditional methods use transfer molding with the application of solid epoxy resin compositions. However, as semiconductor devices become thinner and more densely packed, this method has limitations due to flow defects that occur near fine openings and the potential for damage to some delicate components.

[0003] For this reason, LCM or encapsulation has been developed as a processing technique to help protect electronic devices. Compared to transfer molding, LCM or encapsulation has the advantage that the resin flows easily into narrow gaps and is less likely to damage electronic components. Many semiconductor wafer-level packaging ("WLP") already use LCM to encapsulate thin and delicate devices.

[0004] However, there are many challenges for LCM or encapsulation to meet the commercial volume and reliability demands required by the semiconductor packaging industry, especially WLP.

[0005] Warpage is a common problem found in many cured LCMs or liquid encapsulants. It is especially prevalent in anhydride cured epoxy compositions. As package sizes continue to grow and thicknesses decrease, the warpage problem becomes more severe and may lead to failure to meet process requirements and lead to semiconductor package failure.

[0006] To address the warpage issue, various LCMs or liquid encapsulants have been formulated to lower the modulus and glass transition temperature ("Tg"), but going in this direction reduces the chances that the encapsulated package will pass reliability testing.

[0007] LCMs or liquid encapsulants that cure with anhydrides typically have poor viscosity stability at room temperature or during thermal ramping. Viscosity instability can lead to manufacturing difficulties and process uncertainty.

[0008] Conventional materials used to form molded wafers do not have the desired physical properties to improve the warp resistance of the wafers and do not lend themselves to application with liquid compression molding techniques.

[0009] Attempts have been made to address the problem of warping in the past. For example, U.S. Patent No. 9,263,360 is directed to and claims a thermosetting resin composition comprising a thermosetting resin matrix comprising a combination of an epoxy resin component and an epoxy hardener consisting of a phenolic novolac component, optionally an additional component selected from episulfide resins, oxazines, oxazolines, cyanate esters, maleimides, nadimides, itaconimides, and combinations thereof; a block copolymer; a silica filler; and optionally a catalyst and an accelerator, wherein the block copolymer is an amphiphilic one selected from polystyrene, copolymers made from 1,4-polybutadiene and syndiotactic poly(methyl methacrylate); polymethyl methacrylate-block-polybutyl acrylate-block polymethyl methacrylate copolymers; and combinations thereof. The silica filler constitutes 50 to 90 weight percent of the composition.

[0010] Also, U.S. Patent No. 8,847,415 is directed to and claims a liquid compression molding curable resin composition comprising a curable resin matrix and a curing component comprising a cationic catalyst and an oxidizer, and when cured, the composition exhibits a DSC peak of less than 140° C. and a delta temperature between the DSC onset temperature and the peak of less than 20° C.

[0011] No. 9,263,360 provides a thermosetting resin composition comprising a thermosetting resin matrix, a block copolymer, a silica filler, and a curing component comprising a combination of an anhydride or phenolic resin and an imidizole. Upon curing, the composition has a modulus at room temperature in the range of about 22 GPas or less, a CTEα1 of 10 ppm or less, and a T g1 and T of about 100℃~150℃ g2 The compound exhibits multiple Tgs, including

[0012] Also, as an unrelated art, U.S. Patent No. 6,727,325 is directed to and claims an epoxy resin composition that includes an uncured epoxy resin, a clathrate that includes a tetrakisphenol compound represented by a specific formula, and a compound that reacts with the epoxy groups of the epoxy resin to cure the resin.

[0013] Notwithstanding these efforts, it would be desirable to provide an alternative LCM or encapsulant that has improved viscosity stability at room temperature and can provide improved resistance to wafer warpage, thereby providing end users with multiple options and a solution to the recurring problem of wafer warpage. Summary of the Invention [Means for solving the problem]

[0014] The present invention provides a thermosetting resin composition that can improve viscosity stability and reduce warpage of molded wafers after curing. More specifically, the composition of the present invention is useful as a liquid compression molding encapsulant that maintains the physical properties of the molding compound and has low warpage after compression molding and oven curing.

[0015] The composition exhibits a low storage modulus at room temperature (e.g., less than or equal to about 25 GPa, desirably in the range of about 10 to about 20 GPa, e.g., in the range of about 5 to about 9 GPa, at room temperature), a low coefficient of thermal expansion ("CTE") (α1<15 ppm; α2<30 ppm), and at least one glass transition temperature (Tg greater than about 135° C. by Thermal Mechanical Analysis ("TMA").

[0016] Additionally, and importantly, the composition exhibits less than 30% change in viscosity over 24 hours at room temperature (25° C.) as measured by a rheometer (TI ARES rheometer) and exhibits less than about 3 cm (e.g., less than about 2 cm) warpage after cure under compression molding conditions. This combination of physical properties holds promise for overcoming some of the significant technical hurdles currently facing the semiconductor packaging industry, particularly with respect to viscosity instability of liquid encapsulants and wafer warpage.

[0017] Thus, in one aspect, a thermosetting resin composition is provided, the reaction product of which includes a thermosetting resin matrix (such as an epoxy resin component), a filler, and a curing component that includes a combination of (1) a clathrate that includes a tetrakisphenol compound and (2) a nitrogen-containing curing agent, such as imidazole and its derivatives.

[0018] In another aspect, a method for improving warpage resistance for a molded wafer is provided, the method comprising the steps of: Providing a wafer having one or more silicon chips disposed thereon; providing a thermosetting resin composition as described in contact with the wafer; and exposing the wafer and the thermosetting resin composition to conditions favorable for allowing the thermosetting resin composition to flow around the wafer and cure into a reaction product of the thermosetting resin composition. The cured reaction product can improve the warpage resistance of a molded wafer by about 50%, preferably at least about 65%, and even more preferably at least about 80%, as compared to a molded wafer made using a material other than those disclosed herein. The wafer is comprised of silicon and the composition is disposed on the wafer at a thickness of less than about 50 percent of the thickness of the wafer, such as less than about 33 percent of the thickness of the wafer. [Brief description of the drawings]

[0019] [Figure 1] FIG. 1 illustrates a process flow diagram of a liquid compression molding encapsulation process for wafer level packaging applications. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] (Detailed Description) The thermosetting resin composition described above includes, among other components, a thermosetting resin matrix (such as an epoxy resin component).

[0021] Examples of epoxy resin components include epoxies made from bisphenol A, bisphenol F, bisphenol S, bisphenol E, biphenyl, or combinations thereof. Additionally, two or more different bisphenol epoxies (or hydrogenated versions thereof) within the same type of resin (such as A, F, S, or E) may be used.

[0022] Commercially available examples of bisphenol epoxies suitable for use herein include bisphenol F type epoxies (e.g., RE-404-S from Nippon Kayaku, Japan, and EPICLON 830 (RE1801), 830S (RE1815), 830A (RE1826), and 830W from Dainippon Ink and Chemicals, and RSL 1738 and YL-983U from Resolution), and bisphenol A type epoxies (e.g., YL-979 and 980 from Resolution).

[0023] The above bisphenol epoxies, available from Dai Nippon, are promoted as liquid undiluted epichlorohydrin-bisphenol F epoxies with lower viscosities than conventional epoxies based on bisphenol A epoxies, and have similar physical properties to liquid bisphenol A epoxies. The bisphenol F epoxies have lower viscosities than the bisphenol A epoxies, but otherwise the two types of epoxies are the same, providing a lower viscosity and therefore faster flowing underfill sealant material. The EEW of these four bisphenol F epoxies is 165-180. The viscosity at 25°C is 3,000-4,500 cps (except for RE1801, whose viscosity upper limit is 4,000 cps). The bisphenol A epoxies have an EEW (g / eq) of 180-195 and a viscosity at 25°C of 100-250 cps.

[0024] The bisphenol A epoxies listed above, available from Resolution, are recommended as low chlorine content liquid epoxies. The total chlorine content of RSL-1738 bisphenol A epoxy is reported to be 500-700 ppm, and that of YL-983U is reported to be 150-350 ppm.

[0025] Epoxies suitable for use herein also include polyglycidyl derivatives of phenolic compounds, such as those commercially available under the trade name EPON, e.g., EPON 828, EPON 1001, EPON 1009, EPON 1031 from Resolution; DER 331, DER 332, DER 334, and DER 542 from Dow Chemical Co.; and BREN-S from Nippon Kayaku. Other suitable epoxies include polyepoxides prepared from polyols and the like, and polyglycidyl derivatives of phenol-formaldehyde novolacs, the latter such as DEN 431, DEN 438, and DEN 439 from Dow Chemical. Cresol analogs are also commercially available under the trade name ARALDITE, e.g., ARALDITE ECN 1235, ARALDITE ECN 1273, and ARALDITE ECN 1299 from Ciba Specialty Chemicals Corporation. SU-8 is a bisphenol A type epoxy novolac available from Resolution. Polyglycidyl adducts of amines, aminoalcohols, and polycarboxylic acids are also useful in the present invention, commercially available resins include GLYAMINE 135, GLYAMINE 125, and GLYAMINE 115 from FIC Corporation; ARALDITE MY-720, ARALDITE 0500, and ARALDITE 0510 from Ciba Specialty Chemicals, and PGA-X and PGA-C from Sherwin-Williams Co.

[0026] In addition to bisphenol epoxies, other epoxy compounds may be included in the epoxy component. For example, cycloaliphatic epoxies such as 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarbonate, or hydrogenated versions of bisphenol or biphenyl epoxies can be used.

[0027] Also used are mono-, di-, or polyfunctional reactive diluents to adjust viscosity and / or reduce Tg, such as butyl glycidyl ether, cresyl glycidyl ether, polyethylene glycol glycidyl ether, or polypropylene glycol glycidyl ether. Suitable monofunctional epoxy co-reactive diluents for use herein include those having a viscosity lower than that of the epoxy component, typically less than about 250 cps.

[0028] The monofunctional epoxy co-reactive diluent should have an epoxy group with an alkyl group having from about 6 to about 28 carbon atoms, examples of which include C 6-28 Alkyl glycidyl ether, C 6-28 Fatty acid glycidyl esters, and C 10-28 Alkylphenol glycidyl ethers are included.

[0029] When such monofunctional epoxy co-reactive diluents are included, they should be used in an amount of up to about 5 weight percent to about 15 weight percent, such as about 8 weight percent to about 12 weight percent, based on the total weight of the thermoset resin matrix.

[0030] The epoxy component should be present in the composition in an amount ranging from about 10 weight percent to about 95 weight percent, desirably from about 20 weight percent to about 80 weight percent, for example about 60 weight percent, based on the total weight of the thermosetting resin matrix.

[0031] In addition to the epoxy resin component, other reactive components may be included, such as an episulfide resin component, an oxazine component, an oxazoline component, a cyanate ester component, and / or a maleimide-, nadimide-, or itaconimide-containing component.

[0032] As the episulfide resin, any of the aforementioned epoxies in which the oxirane oxygen atom is replaced with a sulfur atom may be used.

[0033] Oxazines can be encompassed by the following structure:

[0034] [ka] (In the formula, R1 to R8 each independently represent hydrogen, C 1-40 Alkyl, C 2-40 alkenyl, the latter two of which are optionally interrupted by one or more of O, N, S, C=O, COO, or NHC=O, or substituted by one or more of OH, OR, NRR, SH, SR, COOH, COOR, NHCOOH, or NHCOOR, where R is C 1-40 Alkyl, C 2-40 Alkenyl, or C 6-20 aryl; X is a bond broadly selected from alkylene, alkenylene, or arylene, optionally interrupted by one or more of O, NR, S, C=O, COO, or NHC=O, or substituted by one or more of OH, OR, NRR, SH, SR, COOH, COOR, NHCOOH, or NHCOOR, where R is C 1-40 Alkyl, C 2-40 Alkenyl, or C 6-20 aryl; m and n each independently represents 1 or 2; k is 0 to 6.

[0035] The oxazine resin component should be present in the composition in an amount ranging from about 10 weight percent to about 95 weight percent, desirably from about 20 weight percent to about 80 weight percent, for example about 60 weight percent, based on the total weight of the thermosetting resin matrix.

[0036] More specific examples of the oxazine resin component are benzoxazine resins, examples of which may include the following:

[0037] [ka] (wherein o is 1 to 4, X is defined below, and R1 is alkyl, such as methyl, ethyl, propyl, or butyl), or

[0038] [ka] (wherein p is 1 to 4, Y is defined below, and R4 is selected from hydrogen, halogen, alkyl, or alkenyl.)

[0039] X and Y in the above benzoxazine structure can be independently selected from the monovalent or polyvalent groups listed below: - a hydrocarbyl or substituted hydrocarbyl species having typically in the range of about 6 up to about 500 carbon atoms, said hydrocarbyl species being selected from alkyl, alkenyl, alkynyl, cycloalkyl, cycloalkenyl, aryl, alkylaryl, arylalkyl, arylalkenyl, alkenylaryl, arylalkynyl, or alkynylaryl, with the proviso that X can be aryl only when X includes a combination of two or more different species; - a hydrocarbylene or substituted hydrocarbylene species typically having from about 6 up to about 500 carbon atoms, the hydrocarbylene species being selected from alkylene, alkenylene, alkynylene, cycloalkylene, cycloalkenylene, arylene, alkylarylene, arylalkylene, arylalkenylene, alkenylarylene, arylalkynylene, or alkynylarylene; -heterocyclic or substituted heterocyclic species, typically having in the range of from about 6 up to about 500 carbon atoms; polysiloxane, or - polysiloxane-polyurethane block copolymers, as well as A combination of one or more of the above with a linker selected from the following: a covalent bond, -O-, -S-, -NR-, -NR-C(O)-, -NR-C(O)-O-, -NR-C(O)-NR-, -SC(O)-, -SC(O)-O-, -SC(O)-NR-, -OS(O)2-, -OS(O)2-O-, -OS(O)2-NR-, -OS(O)-, -OS(O)-O-, -OS(O)-NR-, -O-NR-C(O)-, -O-NR-C(O)-O-, -O-N R-C(O)-NR-, -NR-OC(O)-, -NR-OC(O)-O-, -NR-OC(O)-NR-, -O-NR-C(S)-, -O-NR-C(S)-O-, -O-NR-C(S)-NR-, -NR-OC(S)-, -N R-OC(S)-O-, -NR-OC(S)-NR-, -OC(S)-, -OC(S)-O-, -OC(S)-NR-, -NR-C(S)-, -NR-C(S)-O-, -NR-C(S)-NR-, -SS(O)2-, -SS(O) 2- O-, -SS(O)2-NR-, -NR-OS(O)-, -NR-OS(O)-O-, -NR-OS(O)-NR-, -NR-OS(O)2-, -NR-OS(O)2-O-, -NR-OS(O)2-NR-, -O-NR-S(O)-, -O-NR-S(O)-O-, -O-NR-S(O)-NR-, -O-NR-S(O)2-O-, -O-NR-S(O)2-NR-, -O-NR-S(O)2-, -OP(O)R2-, -SP(O)R2-, or -NR-P(O)R2-, where each R is independently hydrogen, alkyl, or substituted alkyl.

[0040] As will be readily appreciated by those of skill in the art, when one or more of the above "X" or "Y" bonds cooperate to form an adduct of a benzoxazine group, a wide variety of organic chains can be produced, such as, for example, oxyalkyl, thioalkyl, aminoalkyl, carboxyalkyl, oxyalkenyl, thioalkenyl, aminoalkenyl, carboxyalkenyl, oxyalkynyl, thioalkynyl, aminoalkynyl, carboxyalkynyl, oxycycloalkyl, thiocycloalkyl, aminocycloalkyl, carboxycycloalkyl, oxychloroalkenyl, thiocycloalkenyl, aminocycloalkenyl, carboxycycloalkenyl, heterocyclic, oxyheterocyclic, thioheterocyclic, aminoheterocyclic, carboxyheterocyclic, oxyaryl, thioaryl, aminoaryl, carboxyaryl, heteroaryl, oxyheteroaryl, thioheteroaryl, aminoheteroaryl, carboxyheteroaryl, oxyalkylaryl, thioalkylaryl, aminoalkylaryl, carboxyalkylaryl, oxyarylalkyl, thioarylalkyl, aminoarylalkyl, carboxyhetero ... aryl, oxyarylalkyl, oxyarylalkenyl, thioarylalkenyl, aminoarylalkenyl, carboxyarylalkenyl, oxyalkenylaryl, thioalkenylaryl, aminoalkenylaryl, carboxyalkenylaryl, oxyarylalkynyl, thioarylalkynyl, aminoarylalkynyl, carboxyarylalkynyl, oxyalkynylaryl, thioalkynylaryl, aminoalkynylaryl, or carboxyalkynylaryl, oxyalkylene, thioalkylene, aminoaryl alkylene, carboxyalkylene, oxyalkenylene, thioalkenylene, aminoalkenylene, carboxyalkenylene, oxyalkynylene, thioalkynylene, aminoalkynylene, carboxyalkynylene, oxycycloalkylene, thiocycloalkylene, aminocycloalkylene, carboxycycloalkylene, oxycycloalkenylene, thiocycloalkenylene, aminocycloalkenylene, carboxycycloalkenylene, oxyarylene, thioarylene, aminoarylene, carboxyarylene, oxyalkylarylene,Thioalkylarylene, aminoalkylarylene, carboxyalkylarylene, oxyarylalkylene, thioarylalkylene, aminoarylalkylene, carboxyarylalkylene, oxyarylalkenylene, thioarylalkenylene, aminoarylalkenylene, carboxyarylalkenylene, oxyalkenylarylene, thioalkenylarylene, aminoalkenylarylene, carboxyalkenylarylene, oxyarylalkynylene, thioarylalkynylene, aminoarylalkynylene, carboxy Arylalkynylene, oxyalkynylarylene, thioalkynylarylene, aminoalkynylarylene, carboxyalkynylarylene, heteroarylene, oxyheteroarylene, thioheteroarylene, aminoheteroarylene, carboxyheteroarylene, heteroatom-containing divalent or polyvalent cyclic partial structure, oxyheteroatom-containing divalent or polyvalent cyclic partial structure, thioheteroatom-containing divalent or polyvalent cyclic partial structure, aminoheteroatom-containing divalent or polyvalent cyclic partial structure, or carboxyheteroatom-containing divalent or polyvalent cyclic partial structure, etc.

[0041] The benzoxazine resin component should be present in the composition in an amount ranging from about 10 weight percent to about 95 weight percent, desirably from about 20 weight percent to about 80 weight percent, for example about 60 weight percent, based on the total weight of the thermoset resin matrix.

[0042] As the cyanate ester component, compounds having the following general structural formula can be used:

[0043] [ka] (In the formula, m is 2 to 5; R 1 is an aromatic nucleus-containing residue. 1should contain at least six carbon atoms and may be derived from an aromatic hydrocarbon, such as, for example, benzene, biphenyl, naphthalene, anthracene, pyrene, etc. The aromatic residue may also be derived from a polynuclear aromatic hydrocarbon in which at least two aromatic rings are linked together via a bridging group, such as one in which the bridging member has the structure of the formula:

[0044] [ka] (In the formula, R a and R b are the same or different and each represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. 1 R also contains residues derived from novolac-type phenolic resins, i.e., cyanate esters of these phenolic resins. 1 may further include non-reactive substituents attached to the ring.

[0045] Examples of useful cyanate esters include, for example, 1,3-dicyanatobenzene; 1,4-dicyanatobenzene; 1,3,5-tricyanatobenzene; 1,3-, 1,4-, 1,6-, 1,8-, 2,6- or 2,7-dicyanatonaphthalene; 1,3,6-tricyanatonaphthalene; 4,4'-dicyanato-biphenyl; bis(4-cyanatophenyl)methane and 3,3',5,5'-tetramethyl, bis(4-cyanatophenyl)methane; 2,2-bis(3,5-dichloro-4-cyanatophenyl)propane; 2,2-bis(3,5-dichloro-4-cyanatophenyl)propane; bromo-4-dicyanatophenyl)propane; bis(4-cyanatophenyl)ether; bis(4-cyanatophenyl)sulfide; 2,2-bis(4-cyanatophenyl)propane; tris(4-cyanatophenyl)-phosphite; tris(4-cyanatophenyl)phosphate; bis(3-chloro-4-cyanatophenyl)methane; cyanide novolacs; 1,3-bis[4-cyanatophenyl-1-(methylethylidene)]benzene, and cyanide bisphenol terminated polycarbonates or other thermoplastic oligomers.

[0046] Other cyanate esters include those disclosed in U.S. Pat. Nos. 4,477,629 and 4,528,366, the disclosures of each of which are expressly incorporated herein by reference, those disclosed in British Patent No. 1,305,702, and those disclosed in International Patent Publication No. WO 85 / 02184, the disclosures of each of which are expressly incorporated herein by reference.

[0047] Particularly preferred cyanate esters for use herein are commercially available under the trade name "AROCY" from Hunstman Advanced Materials, Tarrytown, New York [1,1-di(4-cyanatophenylethane)]. The structures of the four preferred "AROCY" cyanate esters are as follows:

[0048] [ka] ; TIFF2025060995000007.tif59166; TIFF2025060995000008.tif36166

[0049] [ka]

[0050] The cyanate ester resin component should be present in the composition in an amount ranging from about 10 weight percent to about 95 weight percent, desirably from about 20 weight percent to about 80 weight percent, for example about 60 weight percent, based on the total weight of the thermoplastic resin matrix.

[0051] As the maleimide, nadimide or itaconimide, compounds having the following respective general structural formulas can be used:

[0052] [ka] (In the formula, m is 1 to 15, p is 0 to 15, and each R 2 is hydrogen or lower alkyl (C 1-5 and J is a monovalent or polyvalent group including organic or organosiloxane groups, and combinations of two or more thereof, such as those defined as "X" and "Y" with respect to the benzoxazine structure above.

[0053] The monovalent or polyvalent groups include hydrocarbyl or substituted hydrocarbyl species that typically have in the range of from about 6 to about 500 carbon atoms. The hydrocarbyl species can be alkyl, alkenyl, alkynyl, cycloalkyl, cycloalkenyl, aryl, alkylaryl, arylalkyl, arylalkenyl, alkenylaryl, arylalkynyl, and alkynylaryl.

[0054] Additionally, X may be a hydrocarbylene or substituted hydrocarbylene species, typically having in the range of from about 6 to about 500 carbon atoms. Examples of hydrocarbylene species include, but are not limited to, alkylene, alkenylene, alkynylene, cycloalkylene, cycloalkenylene, arylene, alkylarylene, arylalkylene, arylalkenylene, alkenylarylene, arylalkynylene, and alkynylarylene.

[0055] The maleimide, itaconamide, or nadimide may be in liquid or solid form.

[0056] In a desirable embodiment, the maleimide, itaconamide, or nadimide functional groups are separated by a polyvalent group having sufficient length and branching to render the maleimide-containing compound in a liquid state. The maleimide, itaconamide, or nadimide compound may include a spacer between the maleimide functional groups that includes a branched alkylene between the maleimide, itaconamide, or nadimide functional groups.

[0057] In the case of maleimide-containing compounds, the maleimide compound is desirably stearylmaleimide, oleylmaleimide, biphenylmaleimide, or 1,20-bismaleimide-10,11-dioctyl-eicosane, or a combination of the above.

[0058] Also in the case of maleimide-containing compounds, the maleimide compounds may be prepared by the reaction of maleic anhydride with a dimeric amide, or may be prepared from aminopropyl-terminated polydimethylsiloxane, polyoxypropyleneamine, polytetramethyleneoxide-di-p-aminobenzoate, or combinations thereof.

[0059] Particularly desirable maleimides and nadimides include the following:

[0060] [ka] (Wherein, R 5 and R 6 are each selected from alkyl, aryl, aralkyl, or alkaryl groups having from about 6 to about 100 carbon atoms, with or without substitution or interruption by members selected from silane, silicon, oxygen, halogen, carbonyl, hydroxyl, ester, carboxylic acid, urea, urethane, carbamate, sulfur, sulfonate, and sulfone.

[0061] Other desirable maleimides, nadimides, and itaconimides include the following:

[0062]

change

[0063]

change

[0064]

change

[0065]

change

[0066]

change

[0067] [ka] TIFF2025060995000030.tif38166 TIFF2025060995000031.tif45166

[0068] The maleimide, nadimide or itaconimide should be present in the composition in an amount ranging from about 10 weight percent to about 95 weight percent, desirably from about 20 weight percent to about 80 weight percent, for example about 60 weight percent, based on the total weight of the thermoset resin matrix.

[0069] Many materials may be useful as the filler component. For example, inorganic fillers may be useful, especially when the coefficient of thermal expansion ("CTE") between the semiconductor chip and the mated substrate needs to be more closely matched. Because the filler affects the CTE, it can be used to reduce the thermal expansion of the cured material, thereby reducing warpage. The filler component often includes reinforcing silica, such as fused spherical silica, and may be untreated or treated to alter the surface chemistry. However, the filler component should include particles having an average particle size distribution in the range of 0.1 to 75 microns, for example, 0.1 to 50 microns. Commercially available examples of such particles are sold by Tatsumori or Denka, Japan. Additionally, nano-sized silica powders may be added, such as those sold under the trade name NANOPOX by Nanoresins, Germany. NANOPOX filler is a monodisperse silica filler dispersion in epoxy resin, at a concentration of up to about 50 weight percent, and is available from Nanoresins, Germany. NANOPOX fillers are generally considered to have a particle size of about 5 nm to about 80 nm.

[0070] Nanoresins also manufactures materials under the trade name NANOPOX E. For example, Nanoresins reports that NANOPOX E branded products allow complete impregnation of otherwise difficult to seal electronic components and provide a wide range of mechanical and thermal properties, including reduced shrinkage and thermal expansion, fracture toughness, and elastic modulus. The table below provides information on four notable NANOPOX E products from Nanoresins.

[0071] [Table 1]

[0072] Nanoresins reports that the use of NANOPOX E brand products can significantly improve key properties in epoxy formulations, such as: -Low compound viscosity compared to conventional reinforcing fillers No settling Increased fracture toughness, impact resistance and elastic modulus -Improved scratch and abrasion resistance ·Reduction of shrinkage and thermal expansion · Improved or at least no adverse effect on many desirable properties such as thermal stability, chemical resistance, glass transition temperature, weatherability, dielectric properties, etc.

[0073] Processability remains substantially unchanged compared to the respective base resins.

[0074] According to the manufacturer, NANOPOX E brand products are colloidal silica sols in an epoxy resin matrix. The dispersed phase consists of surface-modified, spherical SiO2 nanoparticles with a diameter of less than 50 nm and a very narrow particle size distribution, according to the manufacturer. These spheres, only a few nanometers in size, are distributed without agglomeration in the resin matrix. This results in very low-viscosity dispersions with SiO2 contents of up to 40 percent by weight, according to the manufacturer. As reported by the manufacturer, the nanoparticles are chemically synthesized from aqueous sodium silicate solutions. In this process, the binder is not damaged, in contrast to processes in which powdered fillers are dispersed in dissolvers or other equipment that uses high shear energy.

[0075] Other desirable materials for use as the filler component include materials comprised of or consisting of aluminum oxide, silicon nitride, aluminum nitride, silica-coated aluminum nitride, boron nitride, and combinations thereof.

[0076] The filler component, if used, should be used in an amount of from about 50 to about 90 weight percent of the composition, for example, from about 60 to about 90 weight percent, and desirably in the range of from about 70 to about 90 weight percent, based on the total weight of the composition.

[0077] The curing component should be of the latent type.

[0078] The curing component includes a combination of (1) clathrates (such as tetrakisphenol compounds) and (2) nitrogen-containing compounds such as imidazole and its derivatives. Examples of the clathrates include tetrakisphenol compounds, such as 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane, 1,1,2,2-tetrakis(3-methyl-4-hydroxyphenyl)ethane, 1,1,2,2-tetrakis(3,5-dimethyl-4-hydroxyphenyl)ethane, 1,1,2,2-tetrakis(3-chloro-4-hydroxyphenyl)ethane, 1,1,2,2-tetrakis(3,5-di ... 1,1,2,2-Tetrakis(3-bromo-4-hydroxyphenyl)ethane, 1,1,2,2-Tetrakis(3,5-dibromo-4-hydroxyphenyl)ethane, 1,1,2,2-Tetrakis(3-t-butyl-4-hydroxyphenyl)ethane, 1,1,2,2-Tetrakis(3,5-di-t-butyl-4-hydroxyphenyl)ethane, 1,1,2,2-Tetrakis(3-fluoro-4-hydroxyphenyl)ethane, 1,1,2,2-Tetrakis(3,5-difluoro-4-hydroxyphenyl)ethane, 1,1,2 ,2-Tetrakis(3-methoxy-4-hydroxyphenyl)ethane, 1,1,2,2-Tetrakis(3,5-dimethoxy-4-hydroxyphenyl)ethane, 1,1,2,2-Tetrakis(3-chloro-5-methyl-4-hydroxyphenyl)ethane, 1,1,2,2-Tetrakis(3-bromo-5-methyl-4-hydroxyphenyl)ethane, 1,1,2,2-Tetrakis(3-methoxy-5-methyl-4-hydroxyphenyl)ethane, 1,1,2,2-Tetrakis(3-t-butyl-5-methyl 1,1,2,2-tetrakis(3-chloro-5-bromo-4-hydroxyphenyl)ethane, 1,1,2,2-tetrakis(3-chloro-5-phenyl-4-hydroxyphenyl)ethane, 1,1,2,2-tetrakis[(4-hydroxy-3-phenyl)phenyl]ethane, 1,1,3,3-tetrakis(4-hydroxyphenyl)propane, 1,1,3,3-tetrakis(3-methyl-4-hydroxyphenyl)propane, 1,1,3,3-tetrakis(3,5-dimethyl-4-hydroxyphenyl)propane, 1,1,3,3-tetrakis(3-chloro-4-hydroxyphenyl)propane, 1,1,3,3-tetrakis(3,5-dichloro-4-hydroxyphenyl)propane, 1,1,3,3-tetrakis(3-bromo-4-hydroxyphenyl)propane, 1,1,3,3-tetrakis(3,5-dibromo-4-hydroxyphenyl)propane, 1,1,3,3-tetrakis(3-phenyl-4-hydroxyphenyl)propane propane, 1,1,3,3-tetrakis(3,5-diphenyl-4-hydroxyphenyl)propane, 1,1,3,3-tetrakis(3-methoxy-4-hydroxyphenyl)propane, 1,1,3,3-tetrakis(3,5-dimethoxy-4-hydroxyphenyl)propane, 1,1,3,3-tetrakis(3-t-butyl-4-hydroxyphenyl)propane, 1,1,3,3-tetrakis(3,5-di-t-butyl-4-hydroxyphenyl)propane, 1,1,4, 4-Tetrakis(4-hydroxyphenyl)butane, 1,1,4,4-tetrakis(3-methyl-4-hydroxyphenyl)butane, 1,1,4,4-tetrakis(3,5-dimethyl-4-hydroxyphenyl)butane, 1,1,4,4-tetrakis(3-chloro-4-hydroxyphenyl)butane, 1,1,4,4-tetrakis(3,5-dichloro-4-hydroxyphenyl)butane, 1,1,4,4-tetrakis(3-methoxy-4-hydroxyphenyl)butane, 1 , 1,4,4-tetrakis(3,5-dimethoxy-4-hydroxyphenyl)butane, 1,1,4,4-tetrakis(3-bromo-4-hydroxyphenyl)butane, 1,1,4,4-tetrakis(3,5-dibromo-4-hydroxyphenyl)butane, 1,1,4,4-tetrakis(3-t-butyl-4-hydroxyphenyl)butane, 1,1,4,4-tetrakis(3,5-di-t-butyl-4-hydroxyphenyl)butane, and combinations thereof.

[0079] Nitrogen-containing compounds include amines, amides, and imidazoles, to name a few.

[0080] As amines, for example, aliphatic amines, cycloaliphatic and heterocyclic amines, aromatic amines, and modified amines can be used.

[0081] As the aliphatic amine, ethylenediamine, trimethylenediamine, tetramethylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, dipropylethylenediamine, dimethylaminopropylamine, diethylaminopropylamine, trimethylhexamethylenediamine, pentanediamine, bis(2-dimethylaminoethyl)ether, pentamethyldiethylenetriamine, alkyl-t-monoamine, 1,4-diazabicyclo(2,2,2)octane (triethylenediamine), N,N,N',N'-tetramethylhexamethylenediamine, N,N,N',N'-tetramethylpropylenediamine, N,N,N',N'-tetramethylethylenediamine, N,N-dimethylcyclohexylamine, dimethylaminoethoxyethoxyethanol, dimethylaminohexanol, and a part or all of a combination thereof can be used.

[0082] Examples of the alicyclic and heterocyclic amines that can be used include piperidine, piperidine, menthanediamine, isophoronediamine, methylmorpholine, ethylmorpholine, N,N',N"-tris(dimethylaminopropyl)hexahydro-S-triazine, 3,9-bis(3-aminopropyl)-2,4,8,10-tetraoxyspiro(5,5)undecane adduct, N-aminoethylpiperazine, trimethylaminoethylpiperazine, bis(4-aminocyclohexyl)methane, N,N'-dimethylpiperazine, 1,8-diazabicyclo(4,5,0)undecene-7, and any combination thereof.

[0083] As aromatic amines, o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, diaminodiphenylmethane, diaminodiphenylsulfone, benzylmethylamine, dimethylbenzylamine, m-xylylenediamine, pyridine, picolines and combinations thereof can be used.

[0084] The modified polyamine may be an epoxy compound-added polyamine, a Michael reaction-added polyamine, a Mannich reaction-added polyamine, a thiourea-added polyamine, a ketone-blocked polyamine, or a combination thereof.

[0085] The imidazole may be any of imidazole and its derivatives, such as isoimidazole, imidazole, and alkyl-substituted imidazoles, such as 2-methylimidazole, 2-ethyl-4-methylimidazole, 2,4-dimethylimidazole, butylimidazole, 2-heptadecenyl-4-methylimidazole, 2-methylimidazole, 2-undecenylimidazole, 1-vinyl-2-methylimidazole, 2-n-heptadecylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 2-phenylimidazole, 2-ethyl-4-methylimidazole, 1-benzyl-2-methylimidazole, -methylimidazole, 1-propyl-2-methylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-guanaminoethyl-2-methylimidazole, and addition products of imidazole, methylimidazole, and addition products of imidazole and trimellitic acid, 2-n-heptadecyl-4-methylimidazole, and the like (wherein typically each alkyl substituent contains up to about 17 carbon atoms, and preferably up to about 6 carbon atoms);Aryl-substituted imidazoles, such as phenylimidazole, benzylimidazole, 2-methyl-4,5-diphenylimidazole, 2,3,5-triphenylimidazole, 2-styrylimidazole, 1-(dodecylbenzyl)-2-methylimidazole, 2-(2-hydroxyl-4-t-butylphenyl)-4,5-diphenylimidazole, 2-(2-methoxyphenyl)-4,5-diphenylimidazole, 2-(3-hydroxyphenyl)-4,5-diphenylimidazole, 2-(p-dimethyl di(4,5-diphenyl-2-imidazole)-benzene-1,4,2-naphthyl-4,5-diphenylimidazole, 1-benzyl-2-methylimidazole, 2-p-methoxystyrylimidazole, 2-phenyl-4,5-dihydroxymethylimidazole (commercially available under the trade name 2PHZ from Shikoku Kasei, Tokyo, Japan), and combinations thereof may be used;

[0086] Commercially available examples of imidazoles include imidazole from Sigma-Aldrich Corporation, CUREZOL 1B2MZ (benzyl-2-methylimidazole) and CUREZOL 2P4MZ (2-phenyl-4-methylimidazole), each commercially available from Air Products and Chemicals Inc., and ARBADUR 9719-1 (2-ethyl-4-methylimidazole) from Huntsman Advanced Materials Americas Inc.

[0087] The amide compound may be a polyamide obtained by polymerization of a dimer acid and a polyamine, and as an example of the ester compound, an active carbonyl compound such as aryl and thioaryl esters of a carboxylic acid may be used.

[0088] Other nitrogen-containing compounds that can be used include dicyandiamide, guanidine, organic acid hydrazides, diaminomaleonitrile, aminimides, trifluoroboron-piperidine complexes, trifluoroboron-monoethylamine complexes, and combinations thereof.

[0089] The ratio of clathrate to nitrogen-containing compound should be from about 2.5:1 to about 0.5:1 on a molar basis.

[0090] An example of a commercially available hardening component is NISSOCURE manufactured by Nippon Soda.

[0091] The curing component should be included in an amount of from about 0.1 weight percent to about 20 weight percent, such as from about 2 weight percent to about 12 weight percent, based on the total resin composition.

[0092] A variety of additives can be included, as illustrated in the examples below, but of particular note are dispersants such as those commercially available from BYK Chemie under the tradename DYSPERBYK.

[0093] The following examples are provided for illustrative purposes. EXAMPLES

[0094] Reconstructed wafers today are typically constructed to be 8 or 12 inch in diameter. In use, the thermosetting resin composition used to encapsulate the wafer can be applied by pneumatic or piston dispensing onto or around the central portion of the wafer. In addition to reconstructed wafers, the LCMs of the present invention can also be molded onto blank and trench wafers.

[0095] This is followed by exposure to liquid compression molding conditions, e.g., at a temperature of about 110° C. to about 130° C. for about 120 to 420 seconds. See, e.g., FIG. 1. After such exposure, the compression molded wafer may be placed in a conventional oven for a post mold cure at a temperature of about 120° C. to less than about 150° C., e.g., about 120° C. to about 130° C., for about 15 minutes to an hour. Desirably, an 8 inch, 600 μm thick molded wafer should exhibit a bow of less than about 3 mm across the wafer.

[0096] Two control compositions (samples No. 1 and 2) were prepared, one containing a block copolymer (same as in U.S. Pat. No. 9,263,360) and the other not. Sample No. 2 contained FORTEGRA-100 as the block copolymer. Each control composition was based on a thermosetting resin, silica filler, hardener, additives, and colorants. In addition, four compositions (samples No. 3-6) were prepared according to the present invention. All compositions were evaluated for viscosity stability, applied to a carrier with a silicon chip placed thereon, and molded as described above.

[0097] Viscosity stability is measured by placing the composition in a rheometer (ARES) at room temperature and measuring the viscosity profile at various shear rates (T=25°C, gap=0.5 mm, plate diameter=25 mm) at initial time (t=0 hours) and after 24 hours and comparing the viscosity increase.

[0098] The bow of the molded wafer can also be measured using a Nikon NEXIV scanning system, or shadow moiré in the X and Y directions, or estimated with a ruler.

[0099] The warpage of the molded wafers was measured after molding and post-molding processes.

[0100] Referring to Table 1 below, there is shown a control composition (Samples Nos. 1 and 2) and four compositions of the present invention (Samples Nos. 3-6) containing the listed ingredients in the listed amounts.

[0101] [Table 2] TIFF2025060995000034.tif96166

[0102] The compositions were prepared by mixing the listed components with a mechanical mixer until each was observed to dissolve into a homogenous solution. The silica filler was then added and mixing continued at room temperature for approximately 30-60 minutes until a viscous paste of substantially uniform density was achieved. Samples were then transferred to containers until ready for use.

[0103] The composition is applied onto or around the center of a silicon wafer as a carrier. After compression molding at a temperature of about 120°C to less than about 130°C for about 200 to about 400 seconds, the composition is found to be about 60 to about 80% cured, but with a tack-free surface. The wafer thus molded is then placed in a conventional oven at a temperature of about 120°C to about 150°C for about 15 minutes to about 1 hour for a post-mold cure.

[0104] In its intended use, the composition of the present invention can be applied to the active surface of a reconstituted wafer and molded under high pressure (about 98 KN) and elevated temperature of about 110° C. to about 130° C. for about 3 to about 7 minutes. The molded wafer assembly may then be exposed to elevated temperature of about 130° C. to about 150° C. for about 1 to about 2 hours.

[0105] Desirably, an 8 inch, 600 μm thick silicon wafer with 200 μm of cured material should exhibit less than about 3 cm of warpage, and preferably less than about 2 cm, after post mold cure.

[0106] The molded wafer can be peeled, coated with a redistribution layer, solder bumped, and then diced into individual semiconductor packages.

[0107] Referring to Table 2 below, it is shown that certain physical properties observed, including mechanical properties such as elastic modulus, CTE (α1 or 1, α2 or 2), and Tg, were measured by first exposing the samples to compression molding conditions at a temperature of about 120°C to less than about 130°C for about 200 seconds to about 400 seconds, and then further exposing them to a temperature of about 120°C to about 150°C in an oven for about 15 minutes to about 1 hour.

[0108] [Table 3]

[0109] "Standard Test Method for Linear Thermal Expansion of Solid Materials by Thermomechanical Analysis" ASTM International Designation: E831-06, April 2006 issue ("E831-06") describes a test method for "determining the apparent linear thermal expansion coefficient of solid materials using thermomechanical analysis techniques." See Section 1.1 of E831-06. This general method was used to measure CTE α1 or α1.

[0110] "Standard Test Method for Plastics: Dynamic Mechanical Properties: In Flexure (Three-Point Bending)" ASTM International Designation: D5023-01, published November 2001 ("D5023-01") discloses a test method that is "intended to provide a means to determine the elastic modulus as a function of temperature for a wide variety of plastic materials." See Section 1.2 of D5023-01 (emphasis added). This general method was used to measure the storage modulus.

[0111] To achieve high Tg and low warpage in flip chip semiconductor packages, low temperature cure conditions (below about 130°C) and compositions that exhibit fast gelation after exposure to such low temperature cure conditions have been shown to affect warpage. The Tg of the cured composition should be equal to or greater than the temperature used to cure the composition, and the Tg should be greater than 90°C, preferably greater than 125°C. Slower cure or higher temperature compositions result in higher stress free points between the die and substrate set. Warpage at room temperature is induced by cooling a compression molded semiconductor package from the cure temperature to room temperature.

[0112] To achieve reliable thermal cycling performance from -55°C to 125°C for such compression molded semiconductor packages, the liquid compression molded material should have a Tg by TMA greater than 90°C, preferably greater than 125°C, a DSC peak less than 140°C, and a delta temperature between the DSC onset and peak less than 20°C after 260°C reflow.

[0113] As shown in Table 2, one of the control compositions (Sample No. 1) exhibits a high Tg and a low CTE. However, this composition exhibits two problems: (1) a viscosity increase of more than 30% after 24 hours of room temperature storage, and (2) a large warpage of well over 3 cm after curing.

[0114] The other control composition (Sample No. 2) showed a much improved warpage of about 0.4 cm, but this composition also showed a viscosity increase of over 30% after 24 hours of room temperature storage.

[0115] The compositions of the present invention exhibit both improved viscosity stability and reduced warpage. More specifically, Sample No. 3 exhibited less than 30% viscosity increase after 24 hours of room temperature storage. And Sample No. 3 exhibited improved warpage of 2.0 cm.

[0116] Similarly, sample No. 4 also exhibited such viscosity behavior and a warpage of 0.06 cm, while sample No. 5 had similar viscosity and zero warpage.

[0117] Sample No. 6 showed improved viscosity stability after 24 hours of room temperature storage and improved warp resistance at 2.0 cm.

[0118] The compositions of the present invention achieve the following properties: a) When cured, the storage modulus measured by DMA (three-point bending at 5°C / min) at room temperature (25°C) is in the range of 25GPas or less; b) upon curing, CTEα1 is 15 ppm or less and CTEα2 is 30 ppm or less as measured by TMA (at a ramp rate of 5°C / min); c) upon curing, at least one Tg greater than 135°C as measured by TMA (3-point bend, 5°C / min ramp rate); d) As an encapsulating agent, the change in viscosity over 24 hours at room temperature (25°C) is less than 30% as measured using a rheometer (ARES rheometer manufactured by TI).

Claims

1. A thermosetting resin composition comprising a thermosetting resin matrix, a silica filler, and a curing component comprising a combination of a clathrate comprising a combination of a tetrakisphenol compound and a nitrogen-containing curing agent; A composition, wherein the composition exhibits less than about 30% increase in viscosity after 24 hours of room temperature storage, and when cured on a wafer, the composition exhibits less than about 3 cm warpage after oven curing.

2. 10. The composition of claim 1, wherein the composition has the following set of physical properties: (a) a storage modulus in the range of about 25 GPas or less at room temperature; (b) a CTEα1 of 15 ppm or less; (c) a CTE α2 of 30 ppm or less; and (d) Multiple Tg's greater than about 135° C. as measured by TMA.

3. 10. The composition of claim 1, wherein upon curing, the composition exhibits a Tg greater than about 160° C. as measured by TMA and a warpage of less than about 2 cm, the warpage being measured by casting a 200 μm thick layer of the composition onto a 600 μm thick, 8 inch silica wafer at a temperature of about 130° C. to about 150° C. for about 10 minutes to about 1 hour.

4. 10. The composition of claim 1, wherein the wafer is comprised of silicon and the composition is disposed on the wafer at a thickness that is less than about 50 percent of the thickness of the wafer.

5. 13. A method for improving warpage resistance of a molded wafer encapsulated with the composition of claim 1, comprising the steps of: providing a wafer; Providing the thermosetting resin composition of claim 1 in contact with a wafer; and subjecting the wafer and thermosetting resin to conditions favorable to allow the thermosetting resin composition to flow around the wafer and cure into a reaction product of the thermosetting resin composition that can improve warpage resistance by about 50% or more. A method comprising:

6. 6. The method of claim 5, wherein the warp resistance is improved by about 65% or more.

7. 6. The method of claim 5, wherein the warp resistance is improved by about 80% or more.

8. 6. The product formed from the method of claim 5.

9. 2. The composition of claim 1, wherein the thermosetting resin component comprises an epoxy resin component, an episulfide resin component, an oxazine component, an oxazoline component, a cyanate ester component, and / or a maleimide-, nadimide-, or itaconimide-containing component.